The Role of Home Industry in Improving the Economy to Become a Resilient Village : (The Case Study Case of Home Industry in Warugunung Village) - Arie Sulistyawan; Lailatul Maskuroh (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
Starting from July 23 to August 5, 2022, This research was conducted in Warugunung Village. There is a reason to research the village because each hamlet has a different home industry. There are seven hamlets in Warugunung village, including Wonosari, Randegan, Kepuh Gunung, Jolopeto, Kepatihan, Pamotan and Wonokerto hamlets. The purpose of this research is to find out how Home industry activities in each hamlet can survive and what are the ways that homes do. The industry to increase competitiveness so that it continues to increase. The research method used is qualitative. Data analysis carried out during the research is meant to be the research focus and remains given special attention through observation and interview depth, which next will be analyzed qualitatively. The results showed that maintaining capital and increasing the capital made by the home industry owner in each hamlet in Warugunung Village is good by recording meticulously and always counting the goods in and out. In addition, the key to the success of the home industry of each hamlet in the village is among others, maintaining and improving the workforce's existence and marketing the results of the home industry properly and correctly.